Examining the Roles of Environment, Host, and Pathogen in the Host-Pathogen Relationship Between the Oyster Herpesvirus and the Pacific Oyster - Burge, Colleen A. (eScholarship, University of California, 2010)
The Pacific oyster, Crassostrea gigas, an oyster species indigenous to Japan, has been introduced globally becoming the primary species of oyster cultured in many areas of the world. In Tomales Bay, California, seed mortalities have occurred in Pacific oysters nearly annually since 1993, and the oyster herpesvirus (OsHV), a virulent pathogen of larval and juvenile bivalves (particularly known in Pacific oysters) was first detected in 2002. Sentinel field studies (2000-2003) were conducted in Tomales Bay in order to better understand the role of environmental factors (temperature, phytoplankton, and salinity) and oyster health (measured using histology and/or OsHV-specific Polymerase Chain Reaction (PCR)) on Pacific oyster survival. Elevated temperatures were the only environmental factor consistently related to mortalities (2000-2003), and in 2003, elevated temperature means predicted OsHV presence (p < 0.005); OsHV presence predicted mortality (p=0.01). A separate survey conducted in 2003 detected OsHV in multiple species of bivalves grown in Tomales Bay (C. gigas, Ostrea edulis, C. virginica, C. sikamea, Mytilus galloprovincialis, and Venerupis phillipinarum) and C. gigas grown in nearby Drakes Bay using OsHV-specific PCR and/or quantitative PCR (qPCR); qPCR copy numbers were low in each species tested but were significantly greater in C. gigas (p < 0.0001) the only species that appear to be impacted by mortalities. To confirm the infectious etiology of OsHV detected in Tomales Bay, Pacific oyster larvae were exposed to either filtered homogenates from OsHV-infected Pacific oysters in Tomales Bay or uninfected oyster tissue. OsHV was detected and quantified only in oyster larvae exposed to OsHV using qPCR and reverse transcriptase qPCR, and confirmed using transmission electron microscopy. Taken together, data from field and lab-based experiments indicates an infectious disease (OsHV) acts in synergy with temperature to kill Pacific oysters in Tomales Bay, California. Preliminary gene identification of both upregulated host and OsHV genes in larvae exposed to OsHV was conducted using SOLiD sequencing and GeneFishing PCR. Genes identified may provide a foundation to better understand both host response and virus infection, ultimately better defining the hostpathogen relationship between OsHV and Pacific oysters.